2016
DOI: 10.1101/075382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A machine learning classifier trained on cancer transcriptomes detects NF1 inactivation signal in glioblastoma

Abstract: Background: We have identified molecules that exhibit synthetic lethality in cells with loss of the neurofibromin 1 (NF1) tumor suppressor gene. However, recognizing tumors that have inactivation of the NF1 tumor suppressor function is challenging because the loss may occur via mechanisms that do not involve mutation of the genomic locus. Degradation of the NF1 protein, independent of NF1 mutation status, phenocopies inactivating mutations to drive tumors in human glioma cell lines. NF1 inactivation may alter … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A recent study used TCGA data to classify tumors for TP53 inactivation status and found that alterations in multiple genes phenocopy TP53 inactivation, indicating that TP53 mutation status alone is not necessary to infer inactivation of the pathway (Knijnenburg et al 2018). We used a machine learning algorithm to infer TP53 inactivation, as well as NF1 inactivation and Ras pathway activation, from transcriptomes of PDX tumors using classifiers previously trained on TCGA expression data (STAR methods) (Knijnenburg et al 2018; Way et al 2018; Way et al 2017). The TP53 (AUROC = 0.89) and NF1 (AUROC = 0.77) classifiers are both accurate compared to a shuffled gene expression baseline, but performance of the Ras classifier (AUROC = 0.58) was relatively poor (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study used TCGA data to classify tumors for TP53 inactivation status and found that alterations in multiple genes phenocopy TP53 inactivation, indicating that TP53 mutation status alone is not necessary to infer inactivation of the pathway (Knijnenburg et al 2018). We used a machine learning algorithm to infer TP53 inactivation, as well as NF1 inactivation and Ras pathway activation, from transcriptomes of PDX tumors using classifiers previously trained on TCGA expression data (STAR methods) (Knijnenburg et al 2018; Way et al 2018; Way et al 2017). The TP53 (AUROC = 0.89) and NF1 (AUROC = 0.77) classifiers are both accurate compared to a shuffled gene expression baseline, but performance of the Ras classifier (AUROC = 0.58) was relatively poor (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Further, we performed machine learning to classify tumors into TP53 and NF1 active or inactive and we suggest that these scores might be future biomarkers for drug response. These classifiers have been used to identify tumors that may respond to novel agents, including those that target tumors driven by NF1 loss (Way, 2017). Although these machine learning algorithms are not ready for the clinic, the next logical step is to use PDX models to test the predictive nature of classifiers so that in the future, interdisciplinary teams can identify tumors driven by TP53 and/or NF1 loss, evaluate, and compare multiple therapies in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the influence of age and demographic characteristics on the development of NF1 clinical features has the potential to inform more personalized approaches to the identification of symptom "complexes" and ultimately the clinical management of children with NF1. As such, the application of modern computational approaches 43,44 to NF1 facilitated the development of exploratory predictive models with variable performance to identify patients with OPG, ADHD, and plexiform neurofibromas using demographic, clinical features, and EHR data recorded before the clinical manifestation of the feature. The variability in model performance demonstrated herein for diagnosis of OPG and ADHD is most reasonably explained by differences in disease presentation, diagnostic methodology, and differences in clinical expertise of the NF1 clinician.…”
Section: Discussionmentioning
confidence: 99%
“…We accessed RNA-seq data from the UCSC Xena data browser on March 8th, 2016 and archived the data in Zenodo. 30 To facilitate training, we min-maxed scaled RNA-seq data to the range of 0 – 1. We used corresponding clinical data accessed from the Snaptron web server.…”
Section: Methodsmentioning
confidence: 99%